Shaping the Sierra : Nature, Culture, and Conflict in the Changing West - Duane, Timothy P., 1960- (Book collections on Project MUSE., 2000)
Timothy P. Duane documents the impact of rapid population growth on the culture, economy, and ecology of the Sierra Nevada since the late 1960s. He also recommends innovative policies for mitigating the negative effects of future population growth in this spectacular but threatened region, as well as throughout the rural west.